The role of environmental enteric dysfunction in the pathogenesis of Schistosoma mansoni-associated morbidity in school-aged children. - Jacqueline Araújo Fiuza; Susannah Colt; Letícia Gambogi de Ornellas; Leonardo Ferreira Matoso; Andrea Gazzinelli; Jennifer F Friedman; Rodrigo Corrêa-Oliveira (Public Library of Science (PLoS), 2022)
Background Studies have implicated schistosomiasis as a cause of intestinal barrier disruption, a salient feature of environmental enteric dysfunction (EED), as eggs translocate from the sterile bloodstream through the gut wall. We examined the longitudinal impact of praziquantel (PZQ) treatment on a) EED biomarkers and b) Insulin growth factor I (IGF-1), a key driver of childhood linear growth, since EED has been implicated in linear growth stunting. Methodology 290 children infected with S. mansoni in Brazil were treated with PZQ at baseline. EED biomarkers lipopolysaccharide (LPS) and intestinal fatty acid binding-protein (I-FABP) were measured, as well as IGF-1 at baseline, 6 and 12-months. Multivariate regression analysis was applied to assess associations between S. mansoni intensity and plasma biomarkers (LPS, I-FABP, and IGF-1), controlling for potential confounding variables. Principal findings At baseline, S. mansoni infection intensities were 27.2% light, 46.9% moderate, and 25.9% heavy. LPS concentrations were significantly reduced at the 12-month visit compared to baseline (p = 0.0002). No longitudinal changes were observed for I-FABP or IGF-1 in the 6- or 12-month periods following baseline treatment. After 6-months, I-FABP concentration was significantly higher in high vs low intensity (p = 0.0017). IGF-1 concentrations were significantly lower among children with high and moderate vs low intensity infections at each study visit. Conclusions/significance We report that S. mansoni infection impacts LPS, I-FABP and IGF-1. These findings suggest a mechanistic role for EED in schistosomiasis-related morbidities, particularly linear growth.